The influence of extraction of various solvents on chemical properties on Chang 7 shale, Ordos Basin, China - Y. Cao; Y. Cao; Z. Jin; Z. Jin; R. Zhu; R. Zhu; R. Zhu; K. Liu; K. Liu (Solid Earth, 2023)
To explore the effect of various solvents extraction on the chemical property of shale, several lacustrine shale samples from the Chang 7 member of the Upper Triassic Yanchang Formation, Ordos Basin, with maturities, from marginally mature (Tmax=439∘) to late mature (Tmax=456∘), were extracted by using acetone, tetrahydrofuran (THF), carbon disulfide (CS2), and benzene, respectively. Fourier transform infrared spectroscopy (FTIR) was employed to examine the functional groups of the samples before and after extraction with different solvents. The results showed that the extraction yield from shale with THF is significantly higher than that of other solvents, which may be related to the properties of the THF, including the aromatic structure, high boiling point, excellent Hansen solubility parameters, and strong polarity. The total organic carbon (TOC)-normalized yield of the mature sample J1 is significantly higher than that of other samples, which may be related to the fact that the J1 sample is at the peak of hydrocarbon generation; thus, a large number of kerogens were cracked into oil and bitumen. The aromaticity of organic matter (OM) increases with the increase in the maturity. The length of the aliphatic chains of the OM first increased with the increase in the maturity before late maturity stage and then decreased in late maturity stage. The extraction of shale samples with solvents hardly changes the length of aliphatic chains. Higher aromaticity is observed in shale residues after THF extractions than for other solvents (i.e., acetone, CS2, and benzene).